Association of Smoking With Cutaneous Manifestations in Systemic Lupus Erythematosus. Issue 8 (26th July 2013) - Bourré‐Tessier, Josiane; Peschken, Christine A.; Bernatsky, Sasha; Joseph, Lawrence; Clarke, Ann E.; Fortin, Paul R.; Hitchon, Carol; Mittoo, Shikha; Smith, C. Douglas; Zummer, Michel; Pope, Janet; Tucker, Lori; et al.
<x xml:space="preserve">Abstract</x> Objective To examine the association between smoking and cutaneous involvement in systemic lupus erythematosus (SLE). Methods We analyzed data from a multicenter Canadian SLE cohort. Mucocutaneous involvement was recorded at the most recent visit using the Systemic Lupus Erythematosus Disease Activity Index 2000 Update (rash, alopecia, and oral ulcers), Systemic Lupus International Collaborating Clinics/American College of Rheumatology (ACR) Damage Index (alopecia, extensive scarring, and skin ulceration), and the ACR revised criteria for SLE (malar rash, discoid rash, photosensitivity, and mucosal involvement). Multivariate logistic regression models were used to estimate the independent association between mucocutaneous involvement and cigarette smoking, age, sex, ethnicity, lupus duration, medications, and laboratory data. Results In our cohort of 1, 346 patients (91.0% women), the mean ± SD age was 47.1 ± 14.3 years and the mean ± SD disease duration was 13.2 ± 10.0 years. In total, 41.2% of patients were ever smokers, 14.0% current smokers, and 27.1% past smokers. Active mucocutaneous manifestations occurred in 28.4% of patients; cutaneous damage occurred in 15.4%. Regarding the ACR criteria, malar rash was noted in 59.5%, discoid rash in 16.9%, and photosensitivity in 55.7% of patients. In the multivariate analysis, current smoking was associated with active SLE rash (odds ratio [OR] 1.63 [95% confidence interval (95% CI) 1.07, 2.48]). Having ever smoked was associated with ACR discoid rash (OR 2.36 [95% CI 1.69, 3.29]) and photosensitivity (OR 1.47 [95% CI 1.11, 1.95]), and with the ACR total cutaneous score (OR 1.50 [95% CI 1.22, 1.85]). We did not detect any associations between previous smoking and active cutaneous manifestations. No association was found between smoking and cutaneous damage or mucosal ulcers. No interaction was seen between smoking and antimalarials. Conclusion Current smoking is associated with active SLE rash, and ever smoking with the ACR total cutaneous score. This provides additional motivation for smoking cessation in SLE.